THE LEARNING MANAGEMENT BASED ON GAMIFICATION CONCEPTS TO PROMOTE LEARNING ACHIEVEMENT ON STATISTICS AND LEARNING MOTIVATION AMONG MATHAYOMSUKSA 2 STUDENTS - Sawatdee, Fasai; Puangsun, Sompon; Mansong, Ornnicha (Journal of MCU Nakhondhat, 2025)
The objectives of this research were to 1) Determine the efficiency of the learning management based on gamification concepts on statistics for Mathayomsuksa 2 students with the criteria of 70/70, 2) Compare the learning achievement on statistics among Mathayomsuksa 2 students after receiving the learning management based on gamification concepts with the criteria of 70 percent, and 3) Study the learning motivation among Mathayomsuksa 2 students after receiving the learning management based on gamification concepts. This research is quantitative research. The sample of this research consisted of 38 Mathayomsuksa 2 students at Phanomsarakham “Phanom Adun Witthaya” School during the second semester of the academic year 2024, which was obtained by cluster random sampling. The research instruments were 6 lesson plans based on gamification concepts, a learning achievement test on statistics, and a learning motivation test. The statistics used in this research comprised of percentage, mean, standard deviation, and t-test for one sample. The results of the research revealed that 1) The learning management based on gamification concepts on statistics for Mathayomsuksa 2 students had an efficiency of 72.11/74.61, which met the criteria of 70/70. And 2) The learning achievement on statistics among Mathayomsuksa 2 students after receiving the learning management based on gamification concepts was higher than the criteria of 70 percent, with statistical significance at the .05 level. Additionally, 3) The learning motivation among Mathayomsuksa 2 students after receiving the learning management based on gamification concepts was at a high level ( = 3.94 and S.D. = 1.04).